Family meal as a recovery activity : the moderating role of contextual factors - Choo, Julian Jun Hui (Nanyang Technological University, 2020)
Workers face several stressors at work and can experience strain outcomes as a result. Recovery is one mechanism for managing stressors and reducing strain outcomes. Previous studies have focused on recovery experiences in terms of outcomes such as work performance and well-being, while specific recovery activities that lead to recovery have rarely been examined. Thus, this study investigates the family meal as one potential activity in relation to psychological detachment (the recovery experience of not thinking about work, and the strongest in predicting well-being). Survey data was collected from 50 workers, then analyzed using multiple regression and moderated hierarchical regression. Results suggest that family meal frequency is a moderator between work hours and psychological detachment, and that family meal commitment is a moderator between family meal frequency and psychological detachment. Specifically, workers with lower family meal frequency experience a decrease in psychological detachment as work hours increased, and family meal frequency exhibited a positive relationship with psychological detachment for those who have higher family meal commitment. In sum, the study contributes to the recovery literature by demonstrating the family meal as a recovery activity.